Essentials of coordination chemistry a simplified approach with 3D visuals - Bhatt, Vasishta (Academic Press, 2016)
Essentials of Coordination Chemistry: A Simplified Approach with 3D Visuals provides an accessible overview of this key, foundational topic in inorganic chemistry. Thoroughly illustrated within the book and supplemented by online 3D images and videos in full color, this valuable resource covers basic fundamentals before exploring more advanced topics of interest. The work begins with an introduction to the structure, properties, and syntheses of ligands with metal centers, before discussing the variety of isomerism exhibited by coordination compounds, such as structural, geometrical and optical isomerism. As thermodynamics and kinetics provide a gateway to synthesis and reactivity of coordination compounds, the book then describes the determination of stability constants and composition of complexes. Building upon those principles, the resource then explains a wide variety of nucleophilic substitution reactions exhibited by both octahedral and square planar complexes. Finally, the book discusses metal carbonyls and nitrosyls, special classes of compounds that can stabilize zero or even negative formal oxidation states of metal ions. Highlighting preparations, properties, and structures, the text explores the unique type of Metal-Ligand bonding which enable many interesting applications of these compounds. Thoughtfully organized for academic use, Essentials of Coordination Chemistry: A Simplified Approach with 3D Visuals encourages interactive learning. Advanced undergraduate and graduate students, as well as researchers requiring a full overview and visual understanding of coordination chemistry, will find this book invaluable.--Provided by publisher.